The technical efficiency of food industry in Malaysia : an application of stochastic frontier model. - Radam, Alias; Yacob, Mohd Rusli; Kamarulzaman Shah, Saidatul Asima (2008)
This study attempts to measure the status of technical efficiency of food industry in Malaysia using the stochastic frontier model. In an economic where recourses are scarce and opportunities for a new technology are lacking, efficiency studies will be able to show the possibility of raising productivity by improving the industry’s efficiency. The estimated extent of inefficiency can help firms to decide whether to improve efficiency or to develop or adopt new technologies in order to raise the productivity. The computed technical efficiency indices show that the sampled of food industry under study were highly technical inefficient, with an average efficiency ratio of 0.688. Therefore, the results indicated that there is a great potential exists for food industry to further increase the value added using the available input and technology.